THE EFFECT OF SUPPORTING FACILITIES AND BASIC LIQUID LOGISTICS ON BATAM LANAL OPERATIONAL ABILITY - Jamaluddin, Jamaluddin; Haryono, Hendro Yusworo; Hartanto, Yusa Adi (Asian Journal of Aquatic Sciences, 2022)
This research is conducted to find out the influence of liquid logistic supply. In this case, the freshwater and the naval base facilities especially the dock on the operation ability of Batam Naval Base. The method that is used in this research is descriptive quantitative by using a questionnaire in the Likert scale as the research instrument. The questionnaire is given to 63 respondents. The respondents consist of the Batam Naval base and Indonesian warship crews. This research uses some theoretical basis, such as influence theory, competence theory, logistics theory, standardization theory, and operation theory. The researcher uses a multivariate analysis application program by using Statistical Product and Service Solution (SPSS) 25 version for windows. The result of the research indicates that (1) the liquid logistics and the facilities of the Naval Base give a significant effect positively to the ability of Batam Naval Base operation evidenced by the results of the F test which shows a significance value less than 0.05, which is 0.000, (2) the liquid logistics partially give significant positive effects to the ability of Batam Naval Base operation evidenced by the results of the t-test which shows a significance value less than 0.05, which is 0.005, (3) the facilities of Naval Base partially give significant positive effect to the ability of Batam Naval Base operation evidenced by the results of the t-test which shows a significance value less than 0.05, which is 0.000. From the research, we can conclude that the supply of liquid logistics and the facilities of the Naval Base take an important role in the development of Batam Naval Base operation ability fully and partially the development of Batam Naval Base operation ability fully and partially.